2022
DOI: 10.3389/fneur.2022.890499
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effect of plasma total homocysteine levels on cognitive function among hypertensive patients in China: A cross-sectional study

Abstract: BackgroundIncreased plasma total homocysteine (tHcy) is an influencing factor of cognitive impairment in the general population. However, studies on the relationship between the risk of cognitive impairment and plasma tHcy levels in patients with hypertension are limited. This study aimed to explore the association between plasma tHcy levels and cognitive function assessed by MMSE scores among hypertensive patients in China.MethodsA total of 9,527 subjects from the Chinese Hypertension Registry Study participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Homocysteine (Hcy) is an important intermediate sulfur-containing amino acid in the metabolism of methionine and cysteine. A large number of studies have shown that Hcy is an important risk factor for systemic atherosclerosis and cardiovascular disease [ 5 , 6 , 7 , 8 ], and cardiovascular disease is the largest cause of morbidity and mortality associated with DM [ 1 ]. Clinical studies have shown that patients with high blood Hcy have an increased risk of DM complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine (Hcy) is an important intermediate sulfur-containing amino acid in the metabolism of methionine and cysteine. A large number of studies have shown that Hcy is an important risk factor for systemic atherosclerosis and cardiovascular disease [ 5 , 6 , 7 , 8 ], and cardiovascular disease is the largest cause of morbidity and mortality associated with DM [ 1 ]. Clinical studies have shown that patients with high blood Hcy have an increased risk of DM complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%